Capacity Building of Candipuro State Senior High School in Mitigation of Mountain Semeru Eruption, Lumajang District - Adela Oktavia Islami; Pujo Widodo; Ernalem Bangun; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Lumajang Regency has many educational units located in the Semeru eruption disaster risk area. Candipuro High School is a school located in the area of ​​disaster risk III for the eruption of Mount Semeru. Candipuro District does not yet have a disaster-safe education unit. Disaster education in educational units is important to do to improve the capabilities of educational units. This study aims to analyze the implementation of disaster safety education and capacity building at Candipuro High School in mitigating the Mount Semeru eruption disaster. This research method uses quasi-qualitative. Data collection is done by way of interviews, observation and documentation. The results of the study showed that: (1) The implementation of disaster-safe education at Candipuro High School has fulfilled the existing pillars such as safe school facilities, school disaster management, disaster prevention and risk reduction education, but there are still some deficiencies in school disaster management, (2 ) School capacity building is carried out through several programs such as the implementation of disaster-safe education units and participation in disaster response student organizations. The conclusion of this study is that the implementation of disaster-safe education is embodied in disaster safe education unit. In its implementation there are still some shortcomings such as school disaster management that is not good. For capacity building of the five stages, only four stages have been properly fulfilled. In the fifth stage, the evaluation is not yet running. Several dimensions of capacity have emerged such as human resource management, fair participation, program sustainability, partnerships, learning organizations. If the five stages of capacity building and all capacity dimensions appear, then the capacity building at Candipuro High School can run well.